Proceeding of Marine Safety and Maritime Installation (MSMI 2018) 2018
DOI: 10.23977/msmi.2018.82611
|View full text |Cite
|
Sign up to set email alerts
|

Physical Test of Energy Saving Composite Board from Nipah Leaves nypa fruticans

Abstract: Energy-saving architecture is based on the idea of minimizing energy use with science and cutting-edge technology. Nipah leaves is used as a composite material is one of the alternative use of energy-efficient building materials, available enough, and safe for the environment. This research is aimed to know the nipah leaf physical capability when it is done tensile test and bending test to composite material. Tensile and bending tests are the methods used in this study. Based on the result of the test on nipah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In addition, particleboard material based on Nipah palm husk leaves has also been conducted and showed good tensile properties. However, only a few studies which reported the most appropriate mixture formula of Nipah-based particleboard to maintain its flexural strength [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, particleboard material based on Nipah palm husk leaves has also been conducted and showed good tensile properties. However, only a few studies which reported the most appropriate mixture formula of Nipah-based particleboard to maintain its flexural strength [13], [14].…”
Section: Introductionmentioning
confidence: 99%